Cough plate versus cough swab in patients with cystic fibrosis; a pilot study. Issue 6 (21st May 2004) - Maiya, S; Desai, M; Baruah, A; Weller, P; Clarke, J R; Gray, J
Abstract : Background: Accurate identification of lower respiratory tract pathogens is important in the management of cystic fibrosis patients. Aim: To evaluate the cough plate as an alternative method of obtaining respiratory samples for microbiological culture. Methods and Results: Using sputum culture as the "gold standard", the cough plate method identified significantly more positive cases than either dry or moistened cough swabs. Of 20 patients who had a positive sputum culture, 16 had a positive culture on cough plate compared to seven positive cultures each on moistened swab and on dry swab respectively. Conclusions: In this study cough plates were more sensitive than cough swabs in isolating respiratory pathogens in sputum producers. As patients prefer it, the cough plate merits further evaluation, particularly in non-sputum producers.